Inequalities in mining and oil regions of Andean countries - Arellano-Yanguas, J. (Revista Iberoamericana de Estudios de Desarrollo)
The difficulties of translating mineral richness into tangible development outcomes have been widely covered in academic research in the last decade. However, only very recently has the issue of inequalities in the context of extraction received attention. This paper contributes to emerging literature by proposing and applying an analytical framework in which inequalities catalyzed by mining and oil operations are reviewed across three thematic axes (political, socioeconomic, and environmental) and three levels (between institutional actors, between territories, and between groups within a given territory). This systematic analysis uncovers the ways in which the costs and benefits of extraction affect institutions, territories, and social groups differently. In the second part of the paper, it is applied the framework to a mining operation in Peru (Antamina) and an oil field in Colombia (Rubiales). The empirical analysis reveals a set of contextual factors that influence the generation of inequalities.